2018
DOI: 10.1177/0194599817751093
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Ciprofloxacin and Steroids in Mouse Tympanic Membrane Fibroblasts

Abstract: Objective Ciprofloxacin, commonly given as eardrops, has been shown to adversely affect tympanic membrane fibroblasts. Dexamethasone potentiates this effect. A newly available eardrop contains ciprofloxacin and fluocinolone, a more potent steroid. We evaluated the cytotoxic effects of this preparation on mouse tympanic membrane fibroblasts. Study Design Prospective, in vitro. Setting Academic laboratory. Subjects and Methods In experiment 1, fibroblasts were exposed to 1:10 dilutions of commercially available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…As PSB is a component of the commercial cipro + fluocinolone preparation, this likely explains the much higher mouse TM fibroblast cytotoxicity we observed with commercial cipro + fluocinolone than we saw with the same formulation made in our laboratory (ie, without PSB). 5 PSB showed much less cytotoxicity with human TM fibroblasts. We have subsequently assessed commercial cipro + fluocinolone for cytotoxicity in the human TM fibroblast cell line and confirmed the more modest influence of PSB (C.O.D., unpublished observations).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As PSB is a component of the commercial cipro + fluocinolone preparation, this likely explains the much higher mouse TM fibroblast cytotoxicity we observed with commercial cipro + fluocinolone than we saw with the same formulation made in our laboratory (ie, without PSB). 5 PSB showed much less cytotoxicity with human TM fibroblasts. We have subsequently assessed commercial cipro + fluocinolone for cytotoxicity in the human TM fibroblast cell line and confirmed the more modest influence of PSB (C.O.D., unpublished observations).…”
Section: Discussionmentioning
confidence: 90%
“…The cytotoxicity of these “excipients” may have contributed to the toxicity that has previously been attributed to quinolones and steroids in commercial ear drops. 1-6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies on the adverse effects of quinolones on the collagen-rich TM have raised concerns of potentiation by the addition of steroids. 1,2,5,6 However, the potential adverse TM effects by exposure to steroids were raised far earlier. [8][9][10]24 Here, we demonstrated that hydrocortisone, dexamethasone, and fluocinolone decreased survival of mouse and human TM fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6] Both dexamethasone and fluocinolone decreased mouse TM fibroblast survival compared to control, and the combination of dexamethasone or fluocinolone with ciprofloxacin further decreased fibroblast survival. 5 The addition of dexamethasone to ofloxacin or ciprofloxacin also delayed rat TM healing relative to ofloxacin or ciprofloxacin alone. 6 Impaired TM healing following exposure to topical steroids has previously been reported in animals with both dexamethasone and hydrocortisone [8][9][10] and in humans with dexamethasone.…”
mentioning
confidence: 96%